Cerebrovascular disease after placental abruption: A population-based prospective cohort study. (17th September 2019) - Ananth, Cande V.; Hansen, Anne Vinkel; Elkind, Mitchell S.V.; Williams, Michelle A.; Rich-Edwards, Janet W.; Nybo Andersen, Anne-Marie
Abstract : Objective: To test whether abruption during pregnancy is associated with long-term cerebrovascular disease by assessing the incidence and mortality from stroke among women with abruption. Methods: We designed a population-based prospective cohort study of women who delivered in Denmark from 1978 to 2010. We used data from the National Patient Registry, Causes of Death Registry, and Danish Birth Registry to identify women with abruption, cerebrovascular events, and deaths. The outcomes included deaths resulting from stroke and nonfatal ischemic and hemorrhagic strokes. We fit Cox proportional hazards regression models for stroke outcomes, adjusting for the delivery year, parity, education, and smoking. Results: The median (interquartile range) follow-up in the nonabruption and abruption groups was 15.9 (7.8–23.8) and 16.2 (9.6–23.1) years, respectively, among 828, 289 women with 13, 231, 559 person-years of follow-up. Cerebrovascular mortality rates were 0.8 and 0.5 per 10, 000 person-years among women with and without abruption, respectively (hazard ratio [HR] 1.6, 95% confidence interval [CI] 0.9–3.0). Abruption was associated with increased rates of nonfatal ischemic stroke (HR 1.4, 95% CI 1.1–1.7) and hemorrhagic stroke (HR 1.4, 95% CI 1.1–1.9). The association of abruption and stroke was increased with delivery at <34 weeks, when accompanied by ischemic placental disease, and among women with ≥2 abruptions. These associations are less likely to have been affected by unmeasured confounding. Conclusion: Abruption is associated with increased risk of cerebrovascular morbidity and mortality. Disruption of the hemostatic system manifesting as ischemia and hemorrhage may indicate shared etiologies between abruption and cerebrovascular complications.